Rapamycin Induced Autophagy Inhibits Inflammation‐Mediated Endplate Degeneration by Enhancing Nrf2/Keap1 Signaling of Cartilage Endplate Stem Cells. (26th March 2019) - Zuo, Rui; Wang, Yanqiu; Li, Jie; Wu, Junlong; Wang, Wenkai; Li, Bin; Sun, Chao; Wang, Ziwen; Shi, Chunmeng; Zhou, Yue; Liu, Minghan; Zhang, Chao
Abstract: Cartilage endplate (CEP) calcification inhibits the transport of metabolites and nutrients in the intervertebral disk and is an important initiating factor of intervertebral disk degeneration. However, the mechanisms governing CEP degeneration have not been thoroughly elucidated. In this study, we established a mouse CEP degeneration model and showed that autophagy insufficiency caused the degeneration of CEP. We found that the inflammatory cytokine tumor necrosis factor‐α (TNF‐α) increased the level of intracellular reactive oxygen species (ROS) and caused cell senescence and osteogenic differentiation of cartilage endplate stem cells (CESCs), whereas rapamycin‐induced autophagy protected CESCs from TNF‐α‐induced oxidative stress and cell senescence. Furthermore, rapamycin‐induced autophagy helped CESCs maintain the chondrogenic properties and inhibited extracellular matrix protease expression and osteogenic differentiation. Further study revealed that autophagy activated by rapamycin or inhibited by chloroquine influenced the expression and nuclear translocation of Nrf2, thereby controlling the expression of antioxidant proteins and the scavenging of ROS. Taken together, the results indicate that rapamycin‐induced autophagy enhances Nrf2/Keap1 signaling and promotes the expression of antioxidant proteins, thereby eliminating ROS, alleviating cell senescence, reducing the osteogenic differentiation of CESCs, and ultimately protecting CEPs from chronic inflammation‐induced degeneration.Stem Cells 2019;37:828–840 Abstract : Activation of autophagy promotes the nuclear translocation of Nrf2, thus enhancing the expression of antioxidant proteins. Through scavenging of reactive oxygen species in cartilage endplate stem cells induced by inflammatory factors and pressure, cell senescence is alleviated, thus maintaining the chondrogenic characteristics of cartilage endplate stem cells, inhibiting osteogenic differentiation and matrix degradation, and ultimately protecting cartilage endplates from calcification.